1973
DOI: 10.1246/bcsj.46.388
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of 2-Thenoyltrifluoroacetone between Several Organic Solvents and an Aqueous Solution and Its Extraction of Sodium (I) into Methyl Isobutyl Ketone

Abstract: Aqueous solutions containing sodium hydroxide and sodium perchlorate at various mixing ratios, 1 m Na-(OH, ClO4), were equilibrated with several organic solvents containing 2-thenoyltrifluoroacetone (TTA) at 25°. From the measurements of the hydrogen-ion concentration of the aqueous phase, the (KD+l)Ka−1 values, where KD is the distribution constant and Ka is the acid dissociation constant of TTA, were obtained; they were, 107.17(hexane), 107.74 (CCl4), 108.01 (C6H6) and 108.17 (CHCl3). From the values of KD o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…8 Among these, the chelating extraction system is a special method. For example, Serine 9 et al reported that the chelating extraction system has inferior extraction ability for most alkali metal ions except for Li + because Li + can be chelated to form bonds, which are difficult to form with other alkali metal ions (e.g., Na + ). Therefore, the chelating extraction system always exhibits good selectivity for extracting lithium.…”
Section: Introductionmentioning
confidence: 99%
“…8 Among these, the chelating extraction system is a special method. For example, Serine 9 et al reported that the chelating extraction system has inferior extraction ability for most alkali metal ions except for Li + because Li + can be chelated to form bonds, which are difficult to form with other alkali metal ions (e.g., Na + ). Therefore, the chelating extraction system always exhibits good selectivity for extracting lithium.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that TTA forms adduct or ion-pair with trioctylphosphine oxide (TOPO) to create a synergistic effect, which increases the extraction efficiencies of metallic ions. Many researchers studied solvent extraction of metallic ions using TTA and TOPO [7][8][9][10][11][12][13][14][15][16]. Noro and Sekine [11] studied the synergistic extraction of lanthanide using TTA with TOPO or tetrabutylammonium ions (TBA ? )…”
Section: Introductionmentioning
confidence: 99%
“…and reported the distribution coefficient and equilibrium constant. Sekine et al [12][13][14][15] also performed several researches on the solvent extraction of metallic ions with the same extractants. Takazawa et al [16] reported thermodynamic study on the synergistic extraction of cobalt (II) with b-diketone and TTA.…”
Section: Introductionmentioning
confidence: 99%